Transcriptomic profiling of Indian breast cancer patients revealed subtype-specific mRNA and lncRNA signatures - Manjunath, Meghana; Nirgude, Snehal; Mhatre, Anisha; Vemuri, Sai G.; Nataraj, Mallika; Thumsi, Jayanti; Choudhary, Bibha (Frontiers in Genetics, 2022)
Breast cancer (BC) is one of the leading causes of cancer-associated death in women. Despite the progress in therapeutic regimen, resistance and recurrence of Breast cancer have impacted Overall Survival. The present set of signatures such as PAM50 and OncotypeDx did not segregate the Indian Breast samples based on molecular subtypes. This study aimed at finding signatures of long noncoding RNA (lncRNA) and mRNA in Indian Breast cancer patients using RNA-seq. We have analysed the survival based on the menopausal and the hormone status of 380 Indian breast cancer patients. We have sequenced and analysed matched tumour-normal transcriptome of 17 (pre and postmenopausal) Indian breast cancer patients representing 6 different subtypes, i.e., four patients in triple positive, three patients in estrogen receptor-positive (ER+ve), three patients in estrogen and progesterone receptor-positive (ER+ve, PR+ve), two patients in Human epidermal growth factor receptor (Her2+ve), three patients in triple-negative and one patient in ER+ve and Her2 +ve subtypes. We have identified a 25mRNA-27 lncRNA gene set, which segregated the subtypes in our data. Pathway analysis of the DE genes revealed downregulated ECM-interaction and upregulated immune regulation, cell cycle, DNA damage response and repair, and telomere elongation in Premenopausal women. Postmenopausal women showed downregulated metabolism, innate immune system, upregulated translation, sumoylation, and AKT2 activation. Kaplan-Meier survival analysis revealed that menopausal status, grade of the tumour, and hormonal status displayed statistically significant effects (p< 0.05) on the risk of mortality due to breast cancer. Her2+ve patients showed low overall survival. One of the unique lncRNA-mRNA pairs specific to EP-subtype, SNHG12 and EPB41, showed interaction, which correlates with their expression level, SNHG12 is downregulated, and EPB41 is upregulated in EP samples.